Valuation of Companies with a specific reference to Acquisition Valuation - Verma, Himanshu (2005)
The purpose of this dissertation is to examine the various valuation approaches and techniques used in valuing companies and identify what determines a company's value. The dissertation looks at two approaches of valuing companies viz. discounted cash flow valuation approach and the relative valuation approach.